Pengaruh Psikoedukasi Keluarga terhadap Kemampuan Keluarga dalam Merawat Klien Isolasi Sosial - Wiyati, Ruti; Wahyuningsih, Dyah; Widayanti, Esti Dwi (Jurnal Keperawatan Soedirman, 2010)
Social isolation is an individual failure in the interaction with other people because of negative thinking or threatening.The purpose of this study to determine the effect of family psycho education therapy toward family’s ability on caring of client with social isolation. This study used a quasi experiment design by method of pre post test with control group. Respondents of this study were families where 48 clients with social isolation devided as random sampling consist of 24 respondents who got family psycho education therapy as the intervention group and 24 respondents who did not get family psycho education therapy as control group. Analysis univariate data by analyzing variables as descriptive. Analysis bivariate using dependent and independent sample t-test. Family psycho education therapy had been done by 5 sessions. Study result indicated that the average of respondent age were 43,81 females with basic educations and period of caring more than one year. Cognitive abilities in intervention group before therapy were 47,5 and after therapy were 77,5. Cognitive abilities in control group before therapy were 51,25 and after therapy were 64,17. The average of psychomotor abilities in intervention group before therapy were 48,75 and after therapy were 75,83. While the average of psychomotor abilities in control group before therapy were 52,5 and after therapy were 65. From result of bivariate analysis indicated that family psycho education therapy can improve affective and psychomotor abilities in intervention group compared than control group. It was recommended to implement above as family therapy on caring of clients with social isolation